“I Hope When I am Gone, They Will Remember My Stories”: Storytelling Methodology in Educational Research - Thompson, Xandie; Brigham, Susan M.; McDonald, Cassandra (Art/Research International)

(untitled) (University of Alberta, 2025)
This article emphasizes the historical role of storytelling as a way of coming to know. We discuss storytelling in research contexts. We look back on storytelling methodology as a way of looking ahead. Storytelling methodology challenges more conventional approaches to research. It approaches research in a way that is relational, reciprocal, and respectful. Bringing together three studies in the field of lifelong learning, we highlight the storytelling methodology with a focus on intergenerational learning and share key themes that storytelling across generations shares.